Relationship Between Knowledge and Community Stigma with The Level of Family Efficacy in Treating Mental Disorders in The Barong Tongkok Health Center Work Area - Marselinus Febriadi; Badar Badar; Gajali Rahman (Rifa'Institute, 2022)
Introduction: Mental health is one of the most important health problems in the world, including in Indonesia. People still have a low understanding of mental disorders. Objective: to determine the relationship between knowledge and community stigma with the level of family efficacy in treating mental disorders in the Barong Tongkok Health Center Work Area. Methods: The research design is a descriptive correlation with a cross-sectional approach. The population in the Working Area of ??the Barong Tongkok Health Center is 82 people. Using total sampling. The statistical test used is Chi-Square. Result and Discussion: There is a relationship between knowledge and family efficacy in treating mental patients (?-value = 0.00). There is a relationship between community stigma and the level of family efficacy in treating mental patients (?-value = 0.01). Conclusion: The stigma created by society towards people with mental disorders indirectly causes families or people around people with mental disorders to be reluctant to provide proper treatment